1998
DOI: 10.1021/jo971892x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Oxidation of Alcohols to Aldehydes and Ketones by tert-Butyl Hydroperoxide Catalyzed by a Ruthenium Complex of N,N‘,N‘‘-Trimethyl-1,4,7-triazacyclononane

Abstract: An operationally simple method based on [Cn*RuIII(CF3CO2)3·H2O] (Cn* = N,N‘,N‘‘-trimethyl-1,4,7-triazacyclononane) catalyst and 1−1.2 equiv of tert-butyl hydroperoxide as terminal oxidant is effective for selective transformation of alcohols to aldehydes and ketones in methylene chloride. The reaction proceeds in high yield and selectivity. Preparation of benzaldehyde (98% yield) from benzyl alcohol on a 200 mmol scale can be performed without modification of the procedure such as slow addition of the oxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 33 publications
0
39
0
1
Order By: Relevance
“…[27] Species of this nature are also formed by the reaction of TBHP with molybdenum complexes [MoO 2 X 2 L 2 ] (X Cl, Br, CH 3 ), where L 2 is a Lewis base ligand. [18] Hence, we studied the catalytic potential of the derivatised MCM-41 materials in the liquid-phase oxidation of a range of primary and secondary benzylic and aliphatic alcohols, namely benzyl alcohol, sec-phenethyl alcohol, cyclohexanol, cyclooctanol, cyclohexylmethanol, 1-cyclohexylethanol, 1-octanol and (1R,2S,5R)-(À)-menthol.…”
Section: Catalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…[27] Species of this nature are also formed by the reaction of TBHP with molybdenum complexes [MoO 2 X 2 L 2 ] (X Cl, Br, CH 3 ), where L 2 is a Lewis base ligand. [18] Hence, we studied the catalytic potential of the derivatised MCM-41 materials in the liquid-phase oxidation of a range of primary and secondary benzylic and aliphatic alcohols, namely benzyl alcohol, sec-phenethyl alcohol, cyclohexanol, cyclooctanol, cyclohexylmethanol, 1-cyclohexylethanol, 1-octanol and (1R,2S,5R)-(À)-menthol.…”
Section: Catalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…We showed that the presence of pyrazine-2-carboxylic acid strongly increases the catalytic oxidation potential of the dinuclear Fe(III)- [14], so that even alkanes, including ethane and methane, could be oxidised with hydrogen peroxide in acetonitrile. The mononuclear ruthenium(III) complex [(L-Me 3 )Ru(OOCCF 3 ) 3 ] has been reported as an effective catalyst for the epoxidation of alkenes [15] and for the oxidation of alcohols with t-butylhydroperoxide, under mild conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Not only active for alkene epoxidation and alkane oxidation, [Ru III (Me 3 tacn)(OH 2 )(CF 3 CO 2 ) 2 ] + is also an efficient catalyst for oxidation of alcohols with t-BuOOH [50]. A variety of primary alcohols were oxidized to aldehydes with high selectivity in 83-90% yields (Scheme 16, substrate conversions: 67-97%).…”
Section: Oxidation Of Alcoholsmentioning
confidence: 98%
“…In this review, we focus on the Me 3 tacn complexes of ruthenium bearing terminal ruthenium-ligand multiple bonds including ruthenium-oxo and -imido species and their oxygen [16,17,33,34,[45][46][47] and nitrogen atom/group transfer reactions, together with related reactions catalyzed by ruthenium Me 3 tacn complexes, including epoxidation of alkenes [17,48,49], oxidation of alkanes [17,48], alcohols [50,51], aldehydes [51], and arenes [52], oxidative cleavage of C C, C C, and C-C bonds [51], cisdihydroxylation of alkenes [53], and amination of saturated C-H bonds [54]. Also included here are some of our unpublished results on the DFT calculations on reactive Ru O and Ru NTs (Ts = ptoluenesulfonyl) complexes supported by Me 3 tacn, and on C-N bond formation reactions catalyzed by [Ru(Me 3 tacn)(NH 3 ) 3 ] 2+ , and electrochemical oxidation of Ru(III)-NH 2 R to the putative [Ru V NR] 2+ from the [Ru(Me 3 tacn)(H 2 L)] 2+ (H 3 L = ␣-(1-amino-1-methylethyl)-2-pyridinemethanol) complex [55].…”
Section: Introductionmentioning
confidence: 99%